Assessing the Effectiveness of Wet Mount and PCR Methods in Diagnosing Trichomonas vaginalis Infections in Endocervical and Urine samples - Mosa, Zhiman N; Al Jarjari, Senaa Abdullah Ali. (South Eastern European Journal of Public Health, 2024)
Trichomonas vaginalis is the cause of trichomonas’s infection, which is referred to be the global sexually transmitted disease (STD) worldwide. This parasite primarily spreads through sexual activity, though it can also spread through intimate. Vaginal inflammation in females causes a variety of clinical symptoms, such as a profusion of greenish-yellow, frothy, foul-smelling discharge, valvar enlargement, itching, and punctate erythematous lesions of the cervix, commonly referred to as "strawberry cervix." There are numerous scenarios in which women may be sick but not exhibit any symptoms. The purpose of the current study is to compare the diagnostic efficacy of polymerase chain reaction (PCR) and wet mount preparation for detecting T. vaginalis in various sample types, including endocervical discharge, endocervical swabs, and urine, of 300 female patients (married and single), ages ranging from 15 to 62, who were referred to Dohuk Maternity Hospital, Shariya Camp, either inside or outside of Dohuk city. Based on the clinical symptoms of the patients, the diagnosis of parasite infection was validated by microscopically confirming the infection in the laboratory using two methods: PCR and direct wet mount preparation. The study findings demonstrated, out of 240 samples, 61 (25.4%) at Dohuk Maternity Hospital and 15 (25%) out of 60 samples in Shariya Camp were contaminated with T. vaginalis. Of the 300 samples, 74 (24.6%) had wet mount preparation infection, and 75 (25.0%) had PCR infection. In the current study, 42 single women had 10 (23.8%) and 258 married women had 66 (25.5%) infected. The age range of 15 to 25 had a higher infection rate (32.8%).